International Labor Migration Policy of the European Union - Nikolai S. Revenko (Современная Европа)
The cross-border movement of labour is associated with an objective need for the host country to accept and comply with the relevant rules. This problem has always existed for the European Union and its member states due to the attractiveness of the region for migrant workers, relatively high standard of living and the widely diversified sectoral structure of the economy. Based on the analysis of the relevant directives, the article chronologises the stages of regulation of international labour migration in the EU with an emphasis on the present. Close attention is given to the EU regulatory practice of the issues of attracting highly qualified and seasonal labour third-countries workers, students and researchers, facilitating intra-corporate transfers. In this context the regulatory vector in the area of international labour migration to the EU is aimed at obtaining benefits from the influx of the necessary labour force through the creation of favorable conditions for its integration into European society. The implementation of Directive on the conditions of entry and residence of third-country nationals for the purpose of highly qualified employment will depend on the applicable practices of the EU member states. The study reveals the dualism of the economic effects of international labor migration received by the EU at present: positive in the form of a relative reduction in unit costs due to labor components, the flow of technological knowledge and negative ones associated with the displacement of part of local labor resources, the outflow of funds from foreign workers, changes in the structure of aggregate demand, the impact on the level of wages, aggravation of interethnic and interfaith conflicts against the background of a low level of integration of foreigners into local society.